2023
DOI: 10.1212/nxi.0000000000200104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Previous Disease-Modifying Therapy on Treatment Effectiveness for Patients Treated With Ocrelizumab

Abstract: Background and ObjectivesB cell–depleting antibodies were proven as effective strategy for the treatment of relapsing multiple sclerosis (RMS). The monoclonal antibody ocrelizumab was approved in 2017 in the United States and in 2018 in the European Union, but despite proven efficacy in randomized, controlled clinical trials, its effectiveness in the real-world setting remains to be fully elucidated. In particular, most study patients were treatment naive or switched from injectable therapies, whereas oral sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 35 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…Especially, we found no pejorative evolution of disease in patients who previously received fingolimod, as recently suggested. 7 The large sample of patients switching from fingolimod we included (108 vs 38 in the Pfeuffer et al study) and the longer follow-up (3.5 vs 2.3 years) could explain in part the discrepancy with the previous study. In addition, the longer washout period of patients switching from fingolimod in the study by Pfeuffer et al (48 vs 27 days in our study) might explain why some patients in the previous study showed persistent disease reactivation beyond 6 months.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…Especially, we found no pejorative evolution of disease in patients who previously received fingolimod, as recently suggested. 7 The large sample of patients switching from fingolimod we included (108 vs 38 in the Pfeuffer et al study) and the longer follow-up (3.5 vs 2.3 years) could explain in part the discrepancy with the previous study. In addition, the longer washout period of patients switching from fingolimod in the study by Pfeuffer et al (48 vs 27 days in our study) might explain why some patients in the previous study showed persistent disease reactivation beyond 6 months.…”
Section: Discussionmentioning
confidence: 70%
“… 1 - 8 However, real-life studies noted that the risk of disease activity after switching to BCDT may be unequal depending on the prior DMT. 4 - 7 , 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations